An NMR Investigation of Phase Structure and Chain Dynamics in the Polyethylene/Montmorillonite Nanocomposites. (3rd February 2013) - Li, Wei; Hou, Linxi; Chen, Zhongren
Abstract : Novel exfoliated and interacted polyethylene (PE)/montmorillonite (MMT) nanocomposites prepared by in situ polymerization were characterized by solid-state nuclear magnetic resonance (NMR). The phase structure and molecular mobility were investigated by proton and carbon NMR under static and magic-angle spinning (MAS) conditions. The results showed that incorporation of MMT layer enhanced the polyethylene crystallinity behavior. The chain mobility of crystalline phase, interphase and amorphous phase was hindered in the nanocomposites. The phase structure and chain dynamics were also investigated upon changing the temperature. The orthorhombic and monoclinic phases were detected according to the 13 CP/MAS NMR. Quantitative characterization of the phase structure was also conducted by 13 C DP/MAS upon changing the temperature. Finally, the difference in the phase structure and chain dynamics in each phase of PE/nanocomposites was compared based on the NMR results when fiber filler was introduced.